WHAT ARE THE CHALLENGES OF INCREASING THE SUSTAINABILITY OF URBAN LIVELIHOODS? - Neil Whittingham (NALARs, 2009)
AbstraCT. This article places the challenge of rapid urbanisation throughout the world into a perspective that acknowledges inequalities due to economic history. As well as a brief exploration of the site-specific nature of challenges faced, this article seeks to outline the economic and structural obstacles that act as a backdrop to the lives of the poor. Such a perspective can inform attempts to improve the lot of the poor and help in outlining the moral obligation for the powerful to help the poor and vulnerable face up to the issue of Climate Change. Key words: Urbanisation, economic disadvantage, planning, sustainable urban management  AbstraK. Tulisan ini menempatkan tantangan dari urbanisasi yang sangat cepat di seluruh dunia ke dalam perspektif yang diketahui tidak sejajar dengan sejarah ekonomi. Seperti halnya dengan eksplorasi sepintas dari situs khusus alam dari tantangan yang dihadapi, tulisan ini mencoba untuk melihat halangan ekonomi dan struktural bagi masyarakat menengah bawah. Perspektif seperti itu  dapat  menjadi sebuah informasi untuk meningkatkan taraf hidup masyarkat miskin dan membantu dalam merumuskan obligasi moral bagi penguasa. Hal ini tentunya dapat membantu masyarakat miskin dalam menghadapi isu-isu perubahan iklim. Kata Kunci: Urbanisasi, kerugian ekonomi, perencanaan, keberlanjutan manajemen perkotaan